Comparative evaluation of ACetic - MEthanol high salt dissociation approach for single-cell transcriptomics of frozen human tissues - Utkina, Marina; Shcherbakova, Anastasia; Deviatiiarov, Ruslan; Ryabova, Alina; Loguinova, Marina; Trofimov, Valentin; Kuznetsova, Anna; Petropavlovskiy, Mikhail; Salimkhanov, Rustam; Maksimov, Denis; Albert, Eugene; Golubeva, Alexandra; et al. (Frontiers in Cell and Developmental Biology, 2025)
Current dissociation methods for solid tissues in scRNA-seq studies do not guarantee intact single-cell isolation, especially for sensitive and complex human endocrine tissues. Most studies rely on enzymatic dissociation of fresh samples or nuclei isolation from frozen samples. Dissociating whole intact cells from fresh-frozen samples, commonly collected by biobanks, remains a challenge. Here, we utilized the acetic-methanol dissociation approach (ACME) to capture transcriptional profiles of individual cells from fresh-frozen tissue samples. This method combines acetic acid-based dissociation and methanol-based fixation. In our study, we optimized this approach for human endocrine tissue samples for the first time. We incorporated a high-salt washing buffer instead of the standard PBS to stabilize RNA and prevent RNases reactivation during rehydration. We have designated this optimized protocol as ACME HS (ACetic acid-MEthanol High Salt). This technique aims to preserve cell morphology and RNA integrity, minimizing transcriptome changes and providing a more accurate representation of mature mRNA. We compared the ability of enzymatic, ACME HS, and nuclei isolation methods to preserve major cell types, gene expression, and standard quality parameters across 41 tissue samples. Our results demonstrated that ACME HS effectively dissociates and fixes cells, preserving cell morphology and high RNA integrity. This makes ACME HS a valuable alternative for scRNA-seq protocols involving challenging tissues where obtaining a live cell suspension is difficult or disruptive.